Relationship between lenght of undergoing hemodialysis therapy with insomnia in chronic renal failure patients - Bayu Azhar; Deva Arita; Rizka Febtrina; Eka Malfasari; Gita Adelia; Violita Dianatha Puteri; Candra Saputra; M. Zul’irfan (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Complications that are often experienced by patients with chronic kidney failure undergoing hemodialysis are sleep disturbances. Sleep disturbances are experienced by at least 50-80% of patients undergoing hemodialysis > 12 months. The purpose of this study was to determine the relationship between duration of hemodialysis therapy and insomnia in patients with chronic kidney failure at Arifin Achmad Hospital, Riau Province. The research method is a cross sectional approach. The population of this study were all 58 patients undergoing hemodialysis at Arifin Achmad Hospital. The sampling method was purposive sampling. The measuring instrument used in this research is the Insomia Severity Index (ISI) questionnaire. Statistical test using Chi Square test. Results Most of the levels of mild insomnia were 26 respondents (44.8%), moderate insomnia was 21 respondents (36.2%), not clinically significant as many as 8 respondents (13.8%), and severe insomnia was 3 respondents (5.2%). The results of statistical tests obtained p value of 0.487 > (0.05). It can be concluded that there is no relationship between undergoing hemodialysis therapy with insomnia in patients with chronic kidney failure at Arifin Achmad Hospital, Riau Province. Suggestions for further research that can be expected to examine the factors associated with insomnia in patients with chronic kidney failure.